Intravenous immunoglobulin versus methylprednisolone in multisystem inflammatory syndrome in children with COVID-19: an observational study - Masood, Ashfaq; Rasool, Vamiq; Bhat, Mushtaq A. (International Journal of Contemporary Pediatrics, 2022)
Background: Multisystem inflammatory syndrome in children (MIS-C) is temporally associated with SARS CoV 2 infection with a possible immune dysregulation. Presents with a multi organ involvement with dreaded complication of LV dysfunction and a long term sequalae of coronary involvement. Methods: Prospective observational study of a cohort of 35 patients who fulfilled the CDC criteria for MIS-C. Demographic, clinical, lab, echocardiographic, treatment and outcome details were noted and analysed. Results: The 35 children fulfilled CDC definition of MIS-C. Fever was present in 100% cases, rash in 62%, diarrhoea in 57%, RTI in 43%, hypotension in 43% and lymphadenopathy in 19% cases. The 23 patients had moderate MIS-C and 12 patients had severe MIS-C on admission. The 38% had normal contracting heart, 19% had dilated coronaries, 17% had mild LV dysfunction,12% had moderate LV dysfunction,12% had severe LV dysfunction, two patients had prolonged PR interval, one patient had AV block. Four patients had acute kidney injury; one patient had brachial vein thrombosis. 52% patients received combination of methylprednisolone and IVIG while 48% received only methylprednisolone. Defervescence was earlier in IVIG+MPS group compared to MPS group (1.72 days vs 2.8 days [p<0.05]). Improvement in LV dysfunction was earlier in IVIG+MPS group compared to MPS group (33 hours vs 40 hours, p<0.05). At 3 months followup Z score of coronaries was 1.9 (SD=0.125) in LMCA and 1.8 (SD=0.1) in LAD. Conclusions: Patients treated with IVIG+MPS had better outcome compared to MPS only. Older children had more severe disease presentation. Coronary artery dilatation tends to improve with time.